PENGEMBANGAN APLIKASI PEMBELAJARAN IMERSIF BERBASIS VIRTUAL REALITY MENGGUNAKAN METODE MDLC DAN EVALUASI EUQ - Jusia Amanda Ginting; Irwan Sembiring; I Gusti Ngurah Suryantara; Teady Matius Surya Mulyana; Ferry Alamsyah (Infotech: Journal of Technology Information, 2025)
The advancement of technology in the field of Virtual Reality (VR) offers new opportunities for developing more interactive and immersive learning media. One of the main challenges in online learning is the low level of student engagement in the learning process, as well as the tendency for instructional methods to remain passive. Recognizing this gap and the need for a new technological approach that can encourage active participation, this study aims to develop a VR-based learning application called “FirstMetaClass”. This application is designed to simulate a virtual classroom environment to enhance students’ learning experiences. The application development process follows the Multimedia Development Life Cycle (MDLC) method. The quality of the user experience was evaluated using the Extended User Experience Questionnaire (EUQ). The respondents consisted of 42 university students who participated in the application trial and completed the evaluation questionnaire. The results of the study show that all EUQ dimensions achieved an average score above 4.0 on a 1–5 scale. These findings confirm that the “FirstMetaClass” application successfully provides a positive, engaging, and user-friendly learning experience, while creating a classroom atmosphere that closely resembles the real world and fosters a sense of presence for users.